Detrital Chromite from Jack Hills, Western Australia: Signatures of Metamorphism and Constraints on Provenance. (15th June 2021) - Staddon, Leanne G; Parkinson, Ian J; Cavosie, Aaron J; Elliott, Tim; Valley, John W; Fournelle, John; Kemp, Anthony I S; Shirey, Steven B
Abstract: Detrital chromites are commonly reported within Archean metasedimentary rocks, but have thus far garnered little attention for use in provenance studies. Systematic variations of Cr–Fe spinel mineral chemistry with changing tectonic setting have resulted in the extensive use of chromite as a petrogenetic indicator, and so detrital chromites represent good candidates to investigate the petrogenesis of eroded Archean mafic and ultramafic crust. Here, we report the compositions of detrital chromites within fuchsitic (Cr-muscovite rich) metasedimentary rocks from the Jack Hills, situated within the Narryer Terrane, Yilgarn Craton, Western Australia, which are geologically renowned for hosting Hadean (>4000 Ma) zircons. We highlight signatures of metamorphism, including highly elevated ZnO and MnO, coupled with lowered Mg# in comparison with magmatic chromites, development of pitted domains, and replacement of primary inclusions by phases that are part of the metamorphic assemblages within host metasedimentary rocks. Oxygen isotope compositions of detrital chromites record variable exchange with host metasedimentary rocks. The variability of metamorphic signatures between chromites sampled only meters apart further indicates that modification occurred in situ by interaction of detrital chromites with metamorphic fluids and secondary mineral assemblages. Alteration probably occurred during upper greenschist to lower amphibolite facies metamorphism and deformation of host metasedimentary rocks at ∼2650 Ma. Regardless of metamorphic signatures, sampling location or grain shape, chromite cores yield a consistent range in Cr#. Although other key petrogenetic indices, such as Fe2 O3 and TiO2 contents, are complicated in Jack Hills chromites by mineral non-stoichiometry and secondary mobility within metasedimentary rocks, we demonstrate that the Cr# of chromite yields significant insights into their provenance. Importantly, moderate Cr# (typically 55–70) precludes a komatiitic origin for the bulk of chromites, reflecting a dearth of komatiites and intrusive equivalents within the erosional catchment of the Jack Hills metasedimentary units. We suggest that the Cr# of Jack Hills chromite fits well with chromites derived from layered intrusions, and that a single layered intrusion may account for the observed chemical compositions of Jack Hills detrital chromites. Where detailed characterization of key metamorphic signatures is undertaken, detrital chromites preserved within Archean metasedimentary rocks may therefore yield valuable information on the petrogenesis and geodynamic setting of poorly preserved mafic and ultramafic crust.